A Study on Regulating the Residual Stress of Electroplated Cu by Manipulating the Nanotwin Directions - Gangli Yang; Tailong Shi; Liu Chang; Hongjia Zhu; Dongyu Tong; Wending Yang; Zeyuan Li; Liyi Li (Micromachines)
Glass substrate, a new type of substrate with excellent mechanical and electrical properties of glass itself, has great potential to become an ideal platform for heterogeneous integration in chiplet systems for high-performance computing applications. The residual stress of the metal layer generated on the glass surface during the electroplating process is one of the major bottlenecks of glass packaging technologies, resulting in glass-metal layer delamination and glass breakage. This paper demonstrated for the first time a method to regulate the residual stress by manipulating the nanotwin directions of the electroplated Cu. The experimental results show that nanotwins with three different directions (non-directional, vertical, and horizontal) can be manipulated by controlling electroplating conditions (concentration of Cl− and gelatin, stirring speed). The orientations of non-directional, vertical, and horizontal nanotwinned Cu are non-oriented, 110 and 111, respectively. After electroplating, the 111-oriented nanotwinned Cu has the smallest residual stress (39.7 MPa). Annealing can significantly reduce the residual stress of nanotwinned Cu, which has been attributed to the decrease in the geometric necessity dislocation density. 110-oriented nanotwinned Cu had drastic recrystallization, while 111-oriented nanotwinned Cu and non-oriented nanotwinned Cu had only slight recrystallization. After annealing, the residual stress of 111-nt-Cu remains the lowest (29.1 MPa).